2018
DOI: 10.1111/iej.12946
|View full text |Cite
|
Sign up to set email alerts
|

External cervical resorption: part 2 – management

Abstract: Effective management of external cervical resorption (ECR) depends on accurate assessment of the true nature and accessibility of ECR; this has been discussed in part 1 of this 2 part article. This aim of this article was firstly, to review the literature in relation to the management of ECR and secondly, based on the available evidence, describe different strategies for the management of ECR. In cases where ECR is supracrestal, superficial and with limited circumferential spread, a surgical repair without roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
28

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 75 publications
(144 reference statements)
0
80
0
28
Order By: Relevance
“…Predisposing factors associated with external cervical root resorption induced by bleaching include history of trauma or orthodontic treatment both of which can cause inflammatory changes in the periodontium (Patel et al . ,). Another important factor is the application of heat during bleaching which increases diffusion of the bleaching agent (Friedman , Attin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors associated with external cervical root resorption induced by bleaching include history of trauma or orthodontic treatment both of which can cause inflammatory changes in the periodontium (Patel et al . ,). Another important factor is the application of heat during bleaching which increases diffusion of the bleaching agent (Friedman , Attin et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, more research is required to confirm the cause and effect relationship of these suggested aetiological factors (Patel et al . ).…”
Section: Aetiologymentioning
confidence: 97%
“…The presenting features of ECR are highly variable and dependent on several factors including location and degree of progression (Patel et al . ). It commonly presents as an incidental finding on clinical and radiographic examination, though there may be clinical signs of localized gingival inflammation and bleeding, pulpal involvement, or in more advanced cases apical periodontitis (Bergmans et al .…”
Section: Clinical Presentationmentioning
confidence: 97%
“…, Patel et al . 2018a). In addition, the true nature of ECR (fibrovascular and bone‐like tissue) will also be more clearly discernible with CBCT (Gunst et al .…”
Section: Root Resorptionmentioning
confidence: 99%